1995
DOI: 10.1111/j.1365-2273.1995.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on nasal ciliary beat frequency

Abstract: Using a photometric method of measuring ciliary beat frequency, the effect of temperature on ciliary activity was investigated. A linear increase in ciliary beat frequency between 19 degrees and 32 degrees C was found. Between 32 degrees and 40 degrees a plateau was reached in which temperature did not significantly affect frequency and above 40 degrees C the frequency began to decline. It is concluded that nasal cilia are not critically dependent upon temperature in the range 32 degrees and 40 degrees C, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 10 publications
5
44
0
Order By: Relevance
“…The most plausible reason is the peculiar environmental condition of high altitude with low temperature and dry air. The nasal cilia are sensitive to low temperatures and the ciliary beat frequency is known to reduce at lower temperatures [6]. In a study by Salah et al [2], it was demonstrated that breathing dry air at sea level significantly reduces NMTT in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The most plausible reason is the peculiar environmental condition of high altitude with low temperature and dry air. The nasal cilia are sensitive to low temperatures and the ciliary beat frequency is known to reduce at lower temperatures [6]. In a study by Salah et al [2], it was demonstrated that breathing dry air at sea level significantly reduces NMTT in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, it is not known whether this effect is caused by modulation of kinase activity, even though an acidic pH has been shown to inhibit PKA function, 46 or the direct activation of ODAs of the axoneme. 47 Temperature has also been shown in many investigations to influence CBF, most likely through protein kinase C modulation., 36,37,48 Lower temperature tends to slow CBF. 36 CBF is also regulated by mechanical factors.…”
Section: Dynamic Regulationmentioning
confidence: 99%
“…Several rhinopathic conditions may affect both morphology and function in the nasal epithelium, and result in alterations in NMC. These include personal conditions like infection, allergy, nasal obstruction, dust particles, tobacco use, aging [6,9,[19][20][21][22][23][24][25][26] , and environmental conditions like temperature, humidity, altitude and air pollution [27,28] . The effect of age on NMC is under debate.…”
Section: Discussionmentioning
confidence: 99%